New Tullbergiidae mitogenomes as the evidence of sister relationship with Onychiuridae (Hexapoda, Collembola) - Li, Jing-Yang; Godeiro, Nerivania Nunes; Gao, Yan; Bu, Yun; Li, Kai (Zootaxa, 2022)
Members of the order Poduromorpha are mostly small and delicate, many of them are notably smaller than 1 mm. For this reason, studies at the molecular level are still scarce, but modern sequencing technologies are making it possible and the Collembola genetic database have increased significantly in the last ten years. In order to contribute to future studies at the molecular level of the group, we sequenced and annotated three mitogenomes of Tullbergiidae species from China, two of them are newly determined. The mitogenomes of Paratullbergia changfengensis, Metaphorura motuoensis and Mesaphorura yosii have 15,210 bp, 14,873 bp and 14,831 bp in length, respectively, containing 13 protein-coding genes (PCGs), 22 transfer-RNA-coding genes (tRNA), and 2 ribosomal-RNA-coding genes (rRNA) with the ancestral Pancrustacean gene order, typical for most mitogenomes of Collembola. We performed phylogenetic analyses based on 13 PCGs with protein sequences using Bayesian inference and maximum likelihood methods. Our phylogenetic analyses including all available mitogenomes of Poduromorpha and the new mitogenomes consistently confirmed the taxonomical placement of the three Chinese species within Tullbergiidae with high support. The monophyly of the family was confirmed with Onychiuridae as its sister group.